Aspek-Aspek Perkembangan Peserta Didik dalam Perspektif Pendidikan Islam - Sofa, Mutiara; Ajazali, Muhammad Rizki Fauzan (Madani: Jurnal Ilmiah Multidisiplin, 2024)
This article explains aspects of student development from an Islamic education perspective. The aim of this research is to determine aspects of student development, human development from an Islamic perspective, as well as factors that influence student development. This research method uses a qualitative approach with descriptive methods. Data collection procedures use content analysis and library research based on the Al-Qur'an and Hadith. The results of this research explain that there are seven aspects of student development, namely: 1) physical motor development, 2) cognitive and intellectual development, 3) social development, 4) language development, 5) emotional development, 6) personality and artistic development, and 7) moral development and appreciation of religion. There are five human developments in the perspective of the Qur'an, namely: 1) Human growth and development is a gradual and gradual process, 2) human growth and development has a certain pattern, 3) Human development is a cumulative and simultaneous process, 4 ) Human growth and development exceeds the existence of world phenomena, 5) Human growth and development goes through certain critical and sensitive periods. that influence student development. Factors that influence student development include genetic/heredity factors and environmental factors, and congenital factorsÂ